SOFT SKILLS, IN FACING THE NEW NORMAL COVID-19 PANDEMIC IN SAMARINDA CITY COMPANIES - La Ode Hasiara; Yunus Tulak Tandirerung (Bajang Institute, 2025)
Based on the background, the formulation of the problem that has been stated previously, the objectives of this study are. (1) To find out the Soft Skill Ability that influences the New Normal of the COVID-19 Pandemic. (2) To find out the Management influence on the New Normal of the COVID-19 Pandemic. (3) To find out the Information Technology influence on the New Normal of the COVID-19 Pandemic. (3) To find out the Soft Skill Ability, Management and Information Technology influence on the New Normal of the COVID-19 Pandemic. The research method uses a quantitative approach, with a Multiple Linear Regression Model. The results of the study show that all variables in the study, such as: 1) The Soft Skill ability variable has a positive and significant effect on the New Normal variable of the COVID-19 Pandemic. 2) The management variable has a positive and significant effect on the new normal variable of the COVID-19 pandemic, and 3) The information technology variable has a positive and significant effect on the New Normal variable of the COVID-19 Pandemic. And of the three variables, it shows that the third variable is the one that has a more dominant effect on the New Normal variable of the COVID-19 Pandemic.